Analysis of width/height ratio and gingival zenith in patients with bilateral agenesis of maxillary lateral incisor - Pini, Núbia Inocencya Pavesi (2012)
Objective: The purpose of this study was to evaluate the width/length ratio and the gingival zenith (GZ), by means of dental casts and digital caliper, in patients with missing maxillary lateral incisors after treatment. Methods: The sample was composed of 52 subjects divided into 3 groups: BRG (n = 18), patients with bilateral agenesis treated with tooth re-contouring; BIG (n = 10) patients with agenesis treated with implants and CG (n = 24), control group. The data were analyzed using Shapiro-Wilk, Spearman correlation, Wilcoxon, Kruskal-Wallis, t test and ANOVA tests (p < 0. 05). Results: For the width/length ratio of the lateral incisors, BIG presented the lowest mean values (0. 72 right and left), when compared with other groups. However, comparison between groups presented statistically significant differences for the right lateral incisor (BIG x CG) and for the canine (BRG x CG). GZ data evaluation showed the greatest difference for BRG (0. 5 right and 0. 48 left). BIG (0. 95 right and 0. 98 left) and CG (0. 98 right and 0. 8 left) presented more similar values, nevertheless, without statistical difference (p > 0. 05). GZ data for the right and left sides of the smile were not considered statistically different. Conclusion: Although no statistical difference was found in the comparison between the groups, analysis of the descriptive values showed that group BIG showed the greatest difference in values with regard to width/length ratio. Regarding gingival zenith, BRG showed the greatest difference. © 2012 Dental Press Journal of Orthodontics.